Induction of oxidative stress in liver and kidney of rats exposed to Nigerian bonny light crude oil (2010)
The local population of Niger-Delta in the Southern part of Nigeria have used bonny light crude oil (BLCO) as a remedy for various ailments and are exposed to some extent to this widespread environmental contaminant or its metabolites through the food chain. BLCO’s hepatorenal toxicity was studied using oxidative stress indices to elucidate the precise nature and mechanism of action. BLCO was orally administered at concentrations of 0, 200, 400, and 800 mg kg21 to adult male rats for 7 days. After exposure, kidney weight was unaffected, but liver weight decreased significantly at 800 mg kg21 only compared with control. BLCO exposure resulted in dose-dependent elevation of serum aminotransferases, total bilirubin, urea, and creatinine. Activities of superoxide dismutase and catalase decreased significantly, whereas c-glutamyltransferase activity and the level of glutathione increased significantly in BLCO-treated animals compared with control in both liver and kidney of rat. Renal activities of glucose-6- phosphatase and 50-nucleotidase markedly decreased in a dose-dependent manner in BLCO-exposed rats. In addition, the levels of hydrogen peroxide and lipid peroxidation significantly increased, dose dependently, in liver and kidney of BLCO-treated rats compared with control. BLCO-treated rats showed marked degeneration of kidney evident in cortical hemorrhages, tubular necrosis, protein casts, and cellular infiltration. However, no treatment-related liver histopathology was observed. The results suggested that BLCO elicits disruption of antioxidant status and concomitant elevation of hydrogen peroxide and lipid peroxidation differentially in liver and kidney of rats. The hepatorenal toxicity of BLCO could be due to induction of oxidative stress in liver and kidney.